Uji Efektifitas Sistem Smart Green House Bertenaga Surya Untuk Budidaya Tanaman - Syafrima Wahyu; Agnes Yuliana; Mohamad Syafaat (Universitas Sam Ratulangi, 2022)
A greenhouse is one form of optimal environmental controlled monitoring for plant growth. Light intensity, air temperature, humidity, wind speed, and heat transfer, and mass transfer are microclimate parameters that are generally observed. Greenhouses can be integrated with the Internet of Things (IoT) to facilitate monitoring called smart greenhouses in real-time. Previously, a solar-powered IoT integrated plant monitoring system has been designed but its effectiveness is not yet known. The purpose of this study was to test the smart greenhouse system for plant cultivation including watering and providing light by utilizing solar panels as a source of electrical energy for the system. The research was carried out in several stages, namely system design, timer testing, pump testing, and watering and lighting. The effectiveness of the greenhouse system has been successfully tested. The test results show good accuracy. There is a slight difference between the test results and the comparison. However, the difference is still tolerable. The smart greenhouse systems can be used for plant cultivation.Â